Transforming Friendship: An Essay in Honor of Jean Vanier - Reinders, Hans S. (Journal of disability & religion, 2015)
This paper is written to honor Jean Vanier for being awarded with the Templeton Prize 2015. It revisits the topic of friendship in his work. The aim is to show that there is a strong connection in Vanier's views on friendship and his understanding of the providential nature of L'Arche. To highlight this aspect of his thinking, the connection of friendship and providence is contrasted with the modern view that connects friendship with choice. Even though Vanier values Aristotle's views on friendship, he clearly does not follow the ancient philosopher. Vanier emphasizes the transforming nature of friendships in L'Arche, which is very different from Aristotle's conception that in important respects returns in the modern view as friendship as the object of choice.